PENGEMBANGAN MEDIA ZIGZAG BOOK BERBASIS MODEL CIRC UNTUK MENINGKATKAN KEMAMPUAN MENENTUKAN IDE POKOK PARAGRAF PADA SISWA KELAS V SDN 1 TAMANREJO - Ulfa Marya, Allifna; Nugraheti Sismulyasih Sb (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop a Zigzag Book learning media based on the CIRC (Cooperative Integrated Reading and Composition) model to improve the ability to determine the main idea of paragraphs in fifth-grade elementary school students. This research uses the Research and Development (R&D) method adapted from Borg and Gall's development model, which was modified into eight stages. The research subjects were fifth-grade students of SDN 1 Tamanrejo, with 5 students for small-scale trials and 12 students for large-scale trials. Data collection techniques used tests (pretest and posttest) and non-tests (interviews, observations, questionnaires, and documentation). The results showed that the developed Zigzag Book media received a